GABA not only a neurotransmitter: osmotic regulation by GABAAR signaling - Cesetti, Tiziana; Ciccolini, Francesca; Li, Yuting (Frontiers in cellular neuroscience, 2012)
In neurons the anionic channel γ-aminobutyric (GABA) A receptor (GABAAR) plays a central role in mediating both the neurotrophic and neurotransmitter role of GABA. Activation of this receptor by GABA also affects the function of non-neuronal cells in the central nervous system (CNS), as GABAARs are expressed in mature macroglia and in almost all progenitor types, including neural stem cells. The relevance of GABA signalling in non-neuronal cells has been comparatively less investigated than in neurons. However, it is becoming increasingly evident that these cells are direct targets of GABA regulation. In non-neuronal cells GABAAR activation leads to influx or efflux of chloride (Cl-) depending on the electrochemical gradient. Ion transport is indissolubly associated to water fluxes across the plasma membrane and plays a key role in brain physiology. Therefore, GABAAR could affect osmotic tension in the brain by modulating ion gradients. In addition, since water movements also occur through specialized water channels and transporters, GABAAR signalling could affect the movement of water also by regulating the function of the channels and transporters involved, thereby affecting not only the direction of the water fluxes but also their dynamics. This regulation has consequences at the cellular level as it modulates cell volume and activates multiple intracellular signalling mechanisms important for cell proliferation, maturation and survival. It may also have consequences at the systemic level. For example, it may indirectly control neuronal excitability, by regulating the extracellular space and interstitial concentration of Cl-, and contribute to brain water homeostasis. Therefore, GABAergic osmotic regulation should be taken into account during the treatment of pathologies requiring the administration of GABAAR modulators and for the development of therapies for diseases causing water unbalance in the brain.